Analysis of Figurative Language Used in Selected Song Lyrics by Niki Zefanya - Putra, Aidil Syah; Dalpah, Dalpah; Cintya, Novi (Indonesian Journal Publisher, 2024)
This study analyzes of the figurative language used in the song lyrics by Niki Zefanya. This research aims to find out the figurative language used in the lyrics of the song lyrics. This method uses qualitative data to find out the figurative language contained used in selected the lyrics songs entitled